PENGARUH KECERDASAN EMOSIONAL DENGAN ETOS KERJA PEGAWAI PADA PT. BUSSAN AUTO FINANCE MEDAN - Novian, Novian (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
This research aims does emotional intelligence affect work ethos .The population in this research are 44 employees at PT. Bussan Auto Finance Medan. While the samples submitted is 44 employees at PT. Bussan Auto Finance Medan. To discuss the problems it is done data collection library and field research. The results Data collection was done by analysis statistical methods using data processing via SPSS. Itâs found that the determination coefficient R square 0,118 which in this case, 11.8% of the companys work ethic can be explained by variables emotional intelligence. While the rest explained by the other reasons. This means that approximately 11.56% of variable Y is the work ethic can be explained by X in this case emotional intelligence. So 88.44% is not examined. Company should conduct an evaluation and replacement of the order of intelligence the emotional well-working tools and appropriate spatial planning work with the development of technology jobs such as the use of tools workshop were replaced with new ones. In addition to evaluating tools office work, the company should also make improvements to human resources company by way of education and training in accordance with the new technology so they can use it effectively.Keywords: Emotional Intelligence, Work Ethos